Calvinism and religious toleration in the Dutch Golden Age - Hsia, R. Po-chia, 1955-; Nierop, Henk F. K. van (Cambridge University Press, 2002)
Hsia and van Nierop have brought together an international group of leading historians to probe the history and myth of Dutch religious toleration. Their outstanding essays shed new light on the paradox of the strictly Calvinist, yet tolerant, Dutch Republic in the Golden Age.